2014
DOI: 10.1186/2192-5372-3-8
|View full text |Cite
|
Sign up to set email alerts
|

Women-owned family businesses in transitional economies: key influences on firm innovativeness and sustainability

Abstract: This research presents an examination of familial influence on strategic entrepreneurial behaviors within a transitional economic context. Utilizing a large sample of women-led family businesses, the study investigates the relationships between risk-taking propensity, entrepreneurial intensity, and opportunity recognition of the entrepreneur and the innovative orientation of the firm and sustainability. A model of the influences on innovativeness and sustainability in family firms is developed, and the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 71 publications
(86 reference statements)
3
44
2
1
Order By: Relevance
“…In short, a firm that relies on sustainability leads to a greater emphasis on long-term survival. Firms with successfully achieved sustainability can achieve their long-term goal [27] and can better perform in a resource-constrained environment [26,28]. Sustainability is about expanding the financial bottom line into a triple bottom line, which includes environmental and social aspects of corporate performance [29].…”
Section: Introductionmentioning
confidence: 99%
“…In short, a firm that relies on sustainability leads to a greater emphasis on long-term survival. Firms with successfully achieved sustainability can achieve their long-term goal [27] and can better perform in a resource-constrained environment [26,28]. Sustainability is about expanding the financial bottom line into a triple bottom line, which includes environmental and social aspects of corporate performance [29].…”
Section: Introductionmentioning
confidence: 99%
“…These were however centered on the developed economies and the challenges therein. The need of the hour is to understand what scholars have already acknowledged: that policymakers and financial experts in any particular country should not uncritically rely on research results from other countries (Alsos et al, 2010;Gundry et al, 2014). The need to assert this distinction forms the backbone of this research work, emphasizing that India, especially the state of Gujarat, has key contributions to make to any discourse on entrepreneurship, especially if based on gender and family.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since Noseleit (2014) studied women only, he urged for future studies on the topic since "children may play an important role in the observed difference in male and female self-employment rates" (Noseleit 2014, p. 563). The family context may have different impacts for men and women (Gundry et al 2014). There is therefore a need to study the relationship between the number of children at home and self-employment or business start-up rates among men and women separately.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%